2014
DOI: 10.1007/s10600-014-1018-5
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Ginsenoside Rc into (20S)-Rg3 by the Bacterium Leuconostoc sp. BG78

Abstract: Ginsenoside (20S)-Rg 3 is one of the most active minor dammarane glycosides of Panax ginseng C. A. Meyer and exhibits a broad spectrum of biological activity including hepatoprotective, immunostimulating, neuroprotective, and antitumor. It inhibits cell growth of malignant A549 lung carcinoma, U937 lymphoma, LNCaP prostate carcinoma, and SK-HEP-1 hepatoma and is of interest in medicine as a potential antitumor agent [1]. One factor limiting the application of ginsenoside (20S)-Rg 3 is its low content in the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…BG78 and Sphingopyxis sp. BG97, respectively ( Ten et al, 2014a and Ten et al, 2014b ). Sui et al (2020) demonstrated that ginsenoside Rg1 could be thoroughly converted into 20( S/R )-Rh1 and 25-OH-20( S/R )-Rh1 by Cordyceps Sinensis , with a biocatalytic pathway established as Rg1→20( S/R )-Rh1→25-OH-20( S/R )-Rh1, and the molar bioconversion rate for total 25-OH-20( S/R )-Rh1 was 82.5%.…”
Section: The Biotransformation Of Major Ginsenosides Into Minor Ginse...mentioning
confidence: 99%
“…BG78 and Sphingopyxis sp. BG97, respectively ( Ten et al, 2014a and Ten et al, 2014b ). Sui et al (2020) demonstrated that ginsenoside Rg1 could be thoroughly converted into 20( S/R )-Rh1 and 25-OH-20( S/R )-Rh1 by Cordyceps Sinensis , with a biocatalytic pathway established as Rg1→20( S/R )-Rh1→25-OH-20( S/R )-Rh1, and the molar bioconversion rate for total 25-OH-20( S/R )-Rh1 was 82.5%.…”
Section: The Biotransformation Of Major Ginsenosides Into Minor Ginse...mentioning
confidence: 99%